Stochastic Devaluation Risk and the Empirical Fit of Target-Zone Models - Bertol, Giuseppe; Svensson, Lars E. O. (Review of Economic Studies, 1993)
A time-varying stochastic devaluation risk is introduced in a model of exchange rate target zones. The model produces realistic patterns of covariation between exchange rates and interest rate differentials, which previous target zone models have been unable to do. A “drift adjustment” method to estimate devaluation expectations from data is suggested.